THE NORMAL ARCHITECTONICS OF THE GREATER OMENTUM VASCULATURE IN ELDERLY PEOPLE OF BOTH GENDER - Stepanchuk, A.P.; Fedorchenko, I.L.; Pryshliak, A.M.; Piliuhin, A.V.; Shepitko, K.V. (World of Medicine and Biology, 2022)
Variability of topography of arteries and veins of the greater omentum, taken from 20 cavaders of elderly people was investigated by the methods of anatomical preparation and morphometry. The right and left gastro-omental arteries form the superior arterial arch in 15 of 18 cases, and did not anastomose in 3 cases. The inferior arterial arch was present in 1 of 20 cases. The left gastro-omental artery was absent in 2 of 20 cases. The central artery has a greater length and outer diameter both in women and men. The veins, in comparison with the arteries, have a larger outer diameter and one vein accompanies the artery of the same name. The zone of the central, and in its absence – the right and left medial arteries of the greater omentum can be used for obtaining the graft for transplantation in the quadrangular and triangular shapes of the greater omentum of the elderly people.